Toxic Leadership and Psychological Well-Being in Millennial Employees - Alfazilla Jandsri Rita; Sutarto Wijono (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
The rapid development of information technology requires companies to adapt; however, it also poses challenges to the psychological well-being of employees. This study analyses the relationship between toxic leadership and the psychological well-being of millennial employees at Company X, a manufacturing entity. Using a quantitative approach and correlation methods, data were collected from 331 employees via a questionnaire. This study employs the Theory of Toxic Leadership (Schmidt, 2008) and Ryff's Psychological Well-being Model (2008). The findings reveal a significant negative correlation (r = -0.488, p < 0.01), indicating that higher levels of toxic leadership are associated with lower levels of employee psychological well-being. These results emphasise the urgency for organisations to implement leadership training programs to reduce poisonous behaviour and promote employee mental health. This study is expected to contribute to the literature on industrial and organisational psychology and serve as a foundation for further research. Keywords: toxic leadership, psychological well-being, millennial employees, industrial psychology, organisation